Spatial Knock-On Effects of Area-Based Urban Policies: Practices From Utrecht, the Netherlands - Anne Slob; Ronald Van Kempen; Gideon Bolt (European Regional Science Association (ERSA), 2006)
In many West European countries the welfare state is retreating and instruments of urban policy have changed. Urban policies are now often area based, which means that action is taken in a spatially defined area. One of the problems of this approach is that it leads to a so called spatial knock-on effect. This is when an area-based approach causes side effects in other areas, that are not involved in the policy. So far, most interest is in the effects for the targeted area, and less attention is being paid to the side effects for other areas. In our opinion this has to change in order to have sound evaluations of the effectiveness of area based urban policies. The aim of this paper is to take a closer look at the effects of area based urban policies in both targeted areas and non targeted areas from a quantitative and a qualitative perspective. In the quantitative approach we examine how the amount of problems in both targeted and non targeted areas has changed since area based urban policy has been implemented. In the qualitative approach information is gathered by interviewing policymakers to find out in what way they deal with spatial knock-on effects. All of this has been studied in the context of three cities in the Netherlands. In the end of the paper we aim to explain spatial knock-on effects and try to strengthen this explanation with several theoretical insights. We also draw some conclusions for further research that can be useful for policymakers.
Keywords: 330